Renewable production of nylon precursors from lignin - Li, Kaile; Yu, Shijie; Radu, Alexandra; Xu, Yongqing; Md Saad, Juniza; Mohamed, Badr A.; Li, Qinghai; Zhang, Yanguo; Luo, Zhicheng; Zhou, Hui (Cell Press, 2025)
Cyclohexanone and cyclohexanol are critical monomeric precursors in the production of nylon 6 and nylon 66, which are conventionally sourced from petroleum. To reduce the reliance on fossil resources and embrace green chemistry, there is a need to shift to more sustainable feedstocks such as lignin, an abundant aromatic biopolymer. To convert lignin-derived monomers obtained by deconstruction of the polymer into nylon precursors, a selective hydrodeoxygenation (SHDO) step, i.e., demethoxylation and dearomatization, toward cyclohexanone and cyclohexanol needs to be carried out. However, catalytic processes required for this transition, spanning catalyst activity, stability, and product selectivity, remain uncertain. This review delves into recent strides with metal-based catalysts (e.g., ruthenium [Ru], nickel [Ni], and cobalt [Co]) on diverse supports (e.g., metal oxides and carbon materials), exploring reaction conditions (solvent, temperature, and H2 pressure) and proposed mechanisms. It concludes by outlining catalyst challenges and future perspectives for the SHDO reaction, paving the way for sustainable nylon precursor synthesis from lignin.